The Influence of the Snowball Throwing Type Cooperative Learning Model on Student Learning Outcomes in Class IV Energy Resources Material at SD Negeri 22 Banda Aceh - Azzohra, Siti Fatimah; Darnius, Said; Tursinawati, Tusinawati (Universitas Syiah Kuala, 2024)
In this research, learning was found to be less active and less understanding of the material being taught, which was reflected in their reluctance to ask questions because they lacked confidence and the material was still considered difficult, resulting in decreased student learning outcomes. The aim of the problem is to determine the effect of the snowball throwing type cooperative learning model on student learning outcomes in class IV energy resources material at SD Negeri 22 Banda Aceh. The method used is quantitative with the type of experiment with a pre-experimental design. The population taken were all class IV students at SD Negeri 22 Banda Aceh with a sample of class IVB. Data collection with tests in the form of pretest and posttest. Data analysis technique using Paired Samples t-test. The research results prove a significance result (2-tailed) of 0.000. Where 0.000 0.05 so there is an influence of the snowball throwing type cooperative learning model on student learning outcomes in class IV energy resources material at SD Negeri 22 Banda Aceh..